Immediate Care Office as a quality management strategy at the Emergency Service of a hospital in Lima, Peru - Núñez Alcocer, Shirley Alejandra (2023)
Objective: To determine the effectiveness of the implementation of the Immediate Care Office as a quality management strategy at the Emergency Service of a public hospital in Lima, Peru. Materials and methods: An analytical, quasi-experimental, before-and-after study conducted with 338 outpatients from different groups treated at the Emergency Service of Hospital María Auxiliadora. Before and after the implementation of the Immediate Care Office, waiting time, satisfaction—assessed through the modified SERVQUAL questionnaire, which was validated and recommended by the Ministry of Health and administered to the postimplementation group—as well as the relationship between satisfaction and waiting time were evaluated. The analysis was performed using IBM SPSS statistics V25.0, frequencies and percentages, the mean difference of both groups obtained through the Levene’s test, and the nonparametric measurement of the Spearman’s correlation coefficient with a significance level of p < 0.05. Results: The results showed a predominance of the female sex (60.95 %), the 14-to-29-year age range (24.56 %) and the Emergency Severity Index level IV (67.16 %). The average waiting time accounted for 17.70 and 4.27 before and after the office implementation, respectively. Therefore, there was a significant difference after the management strategy (p < 0.00). Out of all outpatients, 56.21 % were satisfied with the implementation of the Immediate Care Office, mainly with the empathy (76.33 %) and responsiveness (69.23 %) dimensions, while reliability was the dimension with the lowest satisfaction score (48.52 %). Additionally, there was a significant inverse correlation between waiting time and satisfaction (p < 0.01 and rho: -0.39). Conclusions: The implementation of the Immediate Care Office at the Emergency Service was effective since it reduced the waiting time, which in turn brought satisfaction to the outpatients.